International audit of simulation use in pre-registration medical radiation science training. Issue 4 (November 2021) - Bridge, P.; Shiner, N.; Bolderston, A.; Gunn, T.; Hazell, L.J.; Johnson, R.; Lawson Jones, G.; Mifsud, L.; Stewart, S.L.; McNulty, J.P.
Abstract: Introduction: Simulation-based education (SBE) can replicate the challenging aspects of real-world clinical environments, while providing a safe and less intimidating setting. Literature supports its use within medical radiation science (MRS) training for safe practice of psychomotor skills, development of problem solving, team working, interpersonal and decision-making skills and embedding awareness of patient safety. This project aimed to quantify usage of SBE resources and activities internationally and to evaluate how this changed during COVID-19 restrictions. Methods: An anonymous online survey tool gathered data relating to programme demographics, simulation resources, simulation activities and future plans. A link to the survey was distributed to programme leads via social media, professional bodies and national networks. Results: A total of 72 responses were received from a range of countries and representing a range of programme structures. Most respondents reported up to 100 h of SBE per student per year with low fidelity resources and image viewing software featuring most prominently. There was low reported engagement of service users within simulation activities. Respondents also indicated that COVID-19 had been a trigger for rapid uptake of simulation resources. Conclusion: SBE forms an important aspect of MRS training internationally with low-fidelity resources being widely deployed. Where available, high fidelity virtual reality and specialised profession-specific resources were used heavily. There was a low level of reported engagement with service users or expert patients in simulation activities. Future research will identify whether the rapid uptake of SBE during COVID-19 continues and clarify the role of service users in SBE provision. Implications for practice: Increased collaboration between MRS education providers may help to improve parity of SBE provision and identify additional opportunities to engage service users within SBE.